Post-vaccination SARS-CoV-2 seroprevalence in children aged 3-11 years and the positivity in unvaccinated children: A retrospective, single-center study - Li, Jing; Ge, Menglei; Dai, Shuzhi; Song, Qinwei; Liu, Weijie; Wang, Ying; Xu, Wenjian; Ma, Lijuan (Frontiers in Immunology, 2022)
Objective To analyze the positivity and levels of SARS-CoV-2 antibodies in vaccinated children to evaluate the humoral immune response of vaccination on pediatric population. Analysis on the causes of antibody positivity in unvaccinated children. Methods A retrospective study was conducted on children who were admitted to the Children’s Hospital Affiliated to Capital Institute of Pediatrics. The clinical data of serological testing of SARS-CoV-2 immunoglobulin M (IgM) and IgG antibodies were collected from SARS-CoV-2 vaccinated or unvaccinated children with no evidence of prior novel coronavirus infection. Chemiluminescence immunoassay was utilized for the in vitro determination of SARS-CoV-2 antibodies. Results A total of 3,321 healthy children aged 6-11 years received two doses of inactivated SARS-CoV-2 vaccine. At 1 month after the second dose, the positive rate (96.5%) and levels [8.039 (interquartile range (IQR), 6.067-9.098)] of SARS-CoV-2 IgG antibodies reached the peak and remained at a high level for 2-3 months, after which the positive rate and level of vaccine-induced IgG antibody gradually decreased. Compared with 1 month after the second dose of vaccine, the positive rate of IgG antibody decreased to 70.4% at 7 months, and the antibody level decreased by 69.0%. A total of 945 children aged 3-5 years received one or two doses of inactivated vaccine. The positive rate and levels of SARS-CoV-2 IgG antibody in participants remained high for 3 months after vaccination. There was no gender-based difference in positive rate of IgG antibody in children aged 3-11 years old (P>0.05). Among the 5,309 unvaccinated children aged 0 day to 11 years, 105 (2.0%) were positive for SARS-CoV-2 IgG antibody, which was associated with passive infusion. The maternal humoral response to COVID-19 vaccination in noninfected pregnant women was transferred through the placenta to the fetus, and some children obtained SARS-CoV-2-positive antibodies through blood transfusion. Conclusions Inactivated SARS-CoV-2 vaccines could induce robust humoral immune response that gradually declined within several months after the second dose. Therefore, it helps to determine whether children receive a booster dose and elicit a long-term memory immune response. Positive SARS-CoV-2 antibodies in unvaccinated children were associated with passive IgG antibody infusion.